Activity in mice of recombinant BCG-EgG1Y162 vaccine for Echinococcus granulosus infection. Issue 1 (2nd January 2016) - Ma, Xiumin; Zhao, Hui; Zhang, Fengbo; Zhu, Yuejie; Peng, Shanshan; Ma, Haimei; Cao, Chunbao; Xin, Yan; Yimiti, Delixiati; Wen, Hao; Ding, Jianbing
Abstract : Cystic hydatid disease is a zoonotic parasitic disease caused by Echinococcus granulosus which is distributed worldwide. The disease is difficult to treat with surgery removal is the only cure treatment. In the high endemic areas, vaccination of humans is believed a way to protect communities from the disease. In this study we vaccinated BALB/c mice with rBCG-EgG1Y162, and then detected the level of IgG and IgE specifically against the recombinant protein by ELISA, rBCG-EgG1Y162 induced strong and specific cellular and humoral immune responses. In vitro study showed that rBCG-EgG1Y162 vaccine not only promote splenocytes proliferation but also active T cell. In addition, the rBCG-EgG1Y162 induced a protection in the mice against secondary infection of Echinococcus granulosus .